Effect of organic fertilization on the growth of lettuce (Lactuca sativa L.) and microbiological activity in Dystrophic Haplic Cambisol (Research, Society and Development, 2023)
The increasing demand for organic fertilization and its economic importance shows to be a great alternative for vegetable producers, as it not only meets the nutrient demands of crops but also helps in the physical, chemical, and biological structures of the soil and reduces dependence on chemical fertilizers. However, more studies are necessary regarding the nutritional potential of these compounds, as well as recommendations for application methods aimed at improving the production system. Therefore, the objective of this study was to evaluate the interaction of soil microorganisms through the attributes of Soil Basal Respiration (SBR), Microbial Biomass (MB), and Metabolic Quotient (qCO2), as well as the yield (g/plant), length (cm), and width (cm) of lettuce, as well as the total number of commercial (NFC) and non-commercial (NFNC) leaves after applying different doses of liquid fertilizer based on bovine manure. The methodology consisted of a completely randomized design with a 5x4 factorial scheme (5 treatments with 4 repetitions). The treatments consisted of T1 (Control), T2 (3.0 L/ha¹ of Organic Fertilizer), T3 (6.0 L/ha¹ of Organic Fertilizer), T4 (9.0 L/ha¹ of Organic Fertilizer), and T5 (12.0 L/ha¹ of Organic Fertilizer). The evaluated attributes showed that there was no significant difference between treatments when SBR, MB, and qCO2 were evaluated. However, regarding plant yield, quadratic and linear regression models were obtained, where the liquid organic fertilizer showed promise. The dose of 9 L/ha was the one that obtained the most positive results related to the plant, as we had an increase in productivity and a decrease in waste.